Epistemological implications of a discussion early 20th century. - Мозгова, Н.Г. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2012)
The theme of the article is the analysis of the debate that unfolded in newspapers and periodicals in Kiev in the early twentieth century.